The Influence of Social Media Use to Work, Total Quality Management, and Organizational Culture on Organizational Performance in Digital-Based Food Processing MSMEs - Siyami, Nely Falahati; Setyadi, Dody; Utaminingtyas, Rara Ririn Budi (Universitas Muria Kudus, 2025)
Advances in technology have encouraged Indonesians to use the internet, but the utilization of the internet for the business purposes in Semarang MSMEs has only reached 60% of the total MSMEs. Meanwhile, organizations need the internet or social media to adjust to existing the market dynamics. The aim of this study is to analyze the influence of Social Media Use to Work, Total Quality Management, Organizational Culture on Organizational Performance. The population is digital food processing MSMEs with a sample of 100 MSMEs obtained through distributing questionaries using purposive sampling technique. The result indicate that SMUW, TQM, and OC have a positive effect on OP. The managerial implication is MSMEs need to utilize social media effectively by creating interesting content, apply TQM principles by understanding customer needs, and build a positive organizational culture by setting a clear vision and missions to improve organizational performance.